PENGGUNAAN KITOSAN-POLIVINIL ALKOHOL (PVA)-KALSIUM KARBONAT SEBAGAI MATRIKS UREA SLOW-RELEASE FERTILIZER (SRF) - Nanda Onky Stefani; Sari Edi Cahyaningrum (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Slow-release fertilizer (SRF) is a method used to improve the efficiency of nutrient absorption, particularly urea, which is essential for plants during the early growth stages. This study aims to develop and characterize SRF urea modified with chitosan–polyvinyl alcohol (PVA) incorporating various concentrations of calcium carbonate. The SRF urea was prepared in membrane form and characterized through swelling and porosity tests, as well as urea release analysis over 30 days using UV-Vis spectrophotometry. The results showed that increasing calcium carbonate concentration affected the SRF’s physical properties and urea release rate. The SRF urea formulation labeled C1 exhibited optimal characteristics, with a swelling capacity of 202,5% and porosity of 15,6%, indicating its ability to regulate water diffusion effectively. SRF urea C1 released 72% of its urea content over 30 days, which was higher than that of formulations C2 and C3, yet still maintained controlled-release behavior. Therefore, a calcium carbonate concentration of 0.01% is considered optimal for producing an SRF urea formulation with both high and controlled urea release, suitable for application as a chitosan–PVA-based slow-release fertilizer.